Reasonable top coal thickness for large cross-section open-off cut in lower-layer mining - Gao, Shigang; Du, Wengang; Liu, Yongliang; Chai, Jing; Gao, Dengyan; Ma, Chenyang; Chen, Jianhua (Frontiers in Earth Science, 2023)
The thickness of top coal is the main factor affecting the stability of the large setup entry under the gob. The 1 -2 lower 203 setup entry of Huojitu Coal Mine was as the background to investigate the top coal rational thickness of the large section setup entry under the gob in slicing mining. The deformation law of the top coal of the large section setup entry under different top coal thicknesses was studied with a similar simulation experiment and numerical simulation. The displacement, stress, and top coal structure of the surrounding rock of the setup entry were observed in situ by using a variety of observation methods. The results show that the plastic zone of the floor in the upper slicing face and the influence of the setup entry excavating are 2.02 m and 1.43m, and the maximum plastic zone of the top coal is 3.45 m. It is conducive to maintain the stability of the setup entry when the top coal thickness is more than 3.45m. According to the results monitored distributed optical fiber, the top coal of the setup entry is to be divided into the roof fall hazard zone and roof fall warning zone. When the top coal thickness is 3.0m, 3.5m, and 4.0m, the deformation law changes from exponential deformation to linear and logarithmic relationship in the roof fall hazard zone, it changes from linear to the logarithmic relationship in the roof fall warning zone. When the thickness of top coal is 3.5m and 4.0m, the subsidence trend of top coal slows down obviously, and the subsidence is only 56% and 39% of that of 3m. The deformation law of top coal measured by the DIC is consistent with that of distributed optical fiber. The average thickness of the top coal reserved in the 1 -2 lower 203 setup entry is 4.0m. The maximum surface subsidence of the top coal setup entry hole is 12mm in the field monitoring. The deformation of the top coal is slight, indicating that the top coal thickness of 3.5-4.0m is reasonable.